Health Reforms in Portugal and Ireland in the Context of Crisis - Popic, T.; Devitt, C.; Asensio, M. (NORFACE Welfare State Futures. Final Conference. European University Institute, Florence (Italy), 24-25 May 2018, 2018)
Why, in the context of economic crisis, do some governments manage to execute their policy plans while others do not? The article contributes to the literature that considers crises as windows of opportunity for introducing unpopular welfare reforms by investigating under which conditions governments are able to take advantage of crises and carry out welfare reforms. It focuses on healthcare reforms proposed in Portugal and Ireland in the context of the recent economic crisis and bailout by the Troika. The plans for healthcare reform in the two countries similarly aimed at the integration of fragmented healthcare systems, but there was a difference in the capacity of the governments to carry out these plans. We argue that this difference is explained by two factors - the level of risk associated with the proposed reforms and the degree of policy concurrence between the international and domestic level. The Irish reform proposal was significantly more politically risky than the Portuguese one as it threatened the healthcare benefits of a large part of the population. The Irish reform plan was also not included in the Troika's recommendations regarding healthcare reform, as they went beyond retrenchment and implied large-scale systemic reform. This lack of policy concurrence between the international and domestic level limited the capacity of Irish policymakers to reduce political risk by externalizing responsibility for healthcare reform to the crisis and international actors.